PKM Digitalisasi UMKM di Nagari Guguak Kabupaten Sijunjung - Fitra, Halkadri; Andi Mesta, Hendri; Mulyani, Erly; Khatimah, Husnil; Yuza Sari, Astri (Universitas Negeri Padang, 2024)
The training on digitalization of SMEs in Nagari Guguak, Sijunjung Regency, aims to enhance the capacity of micro, small, and medium enterprises (SMEs) in leveraging digital technology to grow their businesses. This activity is part of an effort to support the digital-based economic transformation, which can improve the competitiveness of SMEs in the modern era. The training covers topics such as the use of digital platforms for marketing, digital payment systems, and efficient business management through information technology. Participants were also educated on the importance of having a digital presence to expand markets and improve operational efficiency. By involving local SMEs, this program is expected to provide new insights into the vast potential offered by the digital world and help businesses optimize online marketing. The training aims to enable participants to improve their business performance, expand their networks, and reach a wider customer base, contributing to the growth of both the local and national economy. The training was attended by business owners from various sectors, including food, handicrafts, and services in Nagari Guguak..